Multiparameter radar observations of time evolution of convective storms: evaluation of water budgets and latent heating rates - Tong, Hui, author; Knupp, K. R., author; Chandrasekar, V., author; Stalker, James, author; American Meteorological Society, publisher (Colorado State University. Libraries, 1998)
One advantage of dual-polarization radars is the ability to differentiate between water and ice phases in storms. The application of difference reflectivity (ZDP) in the analysis of mixed-phase precipitation is presented. Here, ZDP analysis is used to obtain the fraction of water and ice in mixed-phase precipitation. The techniques developed are applied to data collected on 9 August 1991 during the Convection and Precipitation Electrification experiment. Time series of storm total liquid and ice water contents are computed. The liquid and ice water contents are used in a water budget equation to obtain the net latent heating of the convective storm. It is shown that the latent heating profile shows good correlation with the updraft and electric field increases in the time evolution of the storm.